You signed in with another tab or window. Reload to refresh your session.You signed out in another tab or window. Reload to refresh your session.You switched accounts on another tab or window. Reload to refresh your session.Dismiss alert
One can use t ↦ B(t) = (T-t)/(T-S)⋅a + σ⋅(W(t-S)) + t/(T-S)⋅(b-σ⋅W(T-S)) for a bridge from a at time S to b at time T, as in the uncorrelated case where σ = I.
The text was updated successfully, but these errors were encountered:
One can use
t ↦ B(t) = (T-t)/(T-S)⋅a + σ⋅(W(t-S)) + t/(T-S)⋅(b-σ⋅W(T-S))
for a bridge froma
at timeS
tob
at timeT
, as in the uncorrelated case whereσ = I
.The text was updated successfully, but these errors were encountered: